Substrate characteristics and ablation outcome of left atrial tachycardia in rheumatic mitral valve disease. Issue 8 (12th July 2017) - Chen, Hongwu; Yang, Bing; Ju, Weizhu; Zhang, Fengxiang; Yang, Gang; Gu, Kai; Li, Mingfang; Liu, Hailei; Wang, Zidun; Cao, Kejiang; Chen, Minglong
Abstract: Background: Right atrial tachycardia (AT) is a common arrhythmia postsurgical valve replacement in patients with rheumatic heart disease (RHD). However, the substrate and the mechanism of left AT in such patients and the ablation efficacy is less known. Methods and results: Twenty‐seven RHD patients with AT were enrolled in this study; nine of them (33%) had left AT. Five and four patients had left AT during the first and second procedure, respectively. A spontaneous scar in the left posterior wall was identified in all patients, and obvious anterior scar in three patients. Dual‐roof‐dependent AT was found in three patients and macroreentry AT surrounding right pulmonary vein was identified in one patient, two of whom had left anterior scar. Three patients had AT circuit going around the mitral annulus, one of whom had left anterior scar. Entrainment pacing at different sites confirmed the mechanism of these macroreentries. Two patients had a focal origin, one was localized in posterior wall at the edge of the scar and the other one was originated from the left septum with normal voltage. After a mean follow‐up of 27.4 ± 7.9 months, the left AT group had a similar recurrence rate compared with the right AT group alone (67% vs 56%, P = 0.58). In the left AT group, 11% of patients had AT recurrence and 56% of patients developed atrial fibrillation. Conclusion: Left atrial AT can occur in RHD patients postmitral valve replacement. Catheter ablation is feasible with high acute success rate. The incidence of late development atrial fibrillation is considerable after successful ablation.